Systematics and evolution of predatory flower flies (Diptera: Syrphidae) based on exon‐capture sequencing. (17th October 2022) - Mengual, Ximo; Mayer, Christoph; Burt, Trevor O.; Moran, Kevin M.; Dietz, Lars; Nottebrock, Gaby; Pauli, Thomas; Young, Andrew D.; Brasseur, Marie V.; Kukowka, Sandra; Kelso, Scott; Etzbauer, Claudia; et al.
Abstract: Flower flies (Diptera: Syrphidae) are one of the most species‐rich dipteran families and provide important ecosystem services such as pollination, biological control of pests, recycling of organic matter and redistributions of essential nutrients. Flower fly adults generally feed on pollen and nectar, but their larval feeding habits are strikingly diverse. In the present study, high‐throughput sequencing was used to capture and enrich phylogenetically and evolutionary informative exonic regions. With the help of the baitfisher software, we developed a new bait kit (SYRPHIDAE1.0) to target 1945 CDS regions belonging to 1312 orthologous genes. This new bait kit was successfully used to exon capture the targeted loci in 121 flower fly species across the different subfamilies of Syrphidae. We analysed different amino acid and nucleotide data sets (1302 loci and 154 loci) with maximum likelihood and multispecies coalescent models. Our analyses yielded highly supported similar topologies, although the degree of the SRH (global stationarity, reversibility and homogeneity) conditions varied greatly between amino acid and nucleotide data sets. The sisterhood of subfamilies Pipizinae and Syrphinae is supported in all our analyses, confirming a common origin of taxa feeding on soft‐bodied arthropods. Based on our results, we define Syrphini stat.rev. to include the genera Toxomerus and Paragus . Our divergence estimate analyses with beast inferred the origin of the Syrphidae in the Lower Cretaceous (125.5–98.5 Ma) and the diversification of predatory flower flies around the K–Pg boundary (70.61–54.4 Ma), coinciding with the rise and diversification of their prey. Abstract : We developed a new bait kit (SYRPHIDAE1.0) to target 1945 CDS regions belonging to 1312 orthologous genes using genome reduction methods. Our analyses using maximum likelihood and multispecies coalescent models support the division of Syrphinae into four tribes. We define Syrphini stat.rev. to include the genera Toxomerus and Paragus . Divergence estimate analysis inferred the Syrphidae origin in the Lower Cretaceous and the diversification of predatory flower flies around the K–Pg boundary, coinciding with the diversification of their prey.